Diamond protection for reusable ZnO coated fiber-optic measurement head in optoelectrochemical investigation of bisphenol A. (15th February 2022) - Szczerska, Małgorzata; Kosowska, Monika; Listewnik, Paulina; Rycewicz, Michał; Bechelany, Mikhael; Fleger, Yafit; Fixler, Dror; Jakóbczyk, Paweł
Graphical abstract: Highlights: Optoelectrochemical hybrid system is developed and described. Nanocrystalline diamond sheet(NDS) was transferred on ZnO-coated fiber-optic endface. Simultaneous optical and electrochemical measurements were taken. ZnO layer is prone to bisphenol clogging which can be prevented by NDS protection. NDS secures the ZnO surface it covers and prolongs its lifespan. Abstract: Due to the global problem with plastic contaminating the environment, with bisphenol A (BPA) being one of the highest demand, effective monitoring and purification of the pollutants are required. The electrochemical methods constitute a good solution but, due to polymerization of electrochemical oxidation bisphenol A products and their adsorption to the surfaces, measurement head elements are clogged by the formed film. In this research, we propose a nanocrystalline diamond sheet protection for securing elements in direct contact with bisphenol A during electrochemical processes. The solution was presented on the example of a zinc oxide (ZnO) coating deposited on a fiber-optic end-face by Atomic Layer Deposition. Series of optical and electrochemical measurements were performed in a dedicated hybrid setup. The results show that ZnO can be modified during the electrochemistry leading to the drastic change of its properties. Such degradation did not show in case of nanocrystalline diamond sheet-protected sample proving the solution's effectiveness, giving a possibility of re-using the measurement element and prolonging its lifespan.